Investigations into glass additive manufacturing by selective laser melting and directed energy deposition - Spirrett, Fiona (2021)
Glass is a desirable material for many industrial applications, offering unique properties such as transparency, chemical durability, and high thermal resistance. Current production of complex glass shapes is typically achieved through the use of moulds. Customisation of glass geometries therefore often increases the production cost of bespoke glass pieces. Additive Manufacturing methods are capable of fabricating complex geometries at efficient cost for small production volumes, making customisation cost-effective. The opportunities that AM presents for glass manufacturing could be exploited for a number of applications, including fabrication of customised microfluidic devices, and bespoke décor for high value glass packaging. The potential applications for additively manufactured glass parts have driven research and industry to face the associated challenges, such as thermal stresses from high temperature gradients causing parts to crack or fracture, high transmittance in the near infrared (NIR) range reducing laser absorption at certain wavelengths, and porosities and cracking compromising transparency.